Hemostatic Gelatin-Alginate Hydrogels Modified with Humic Acids and Impregnated with Aminocaproic Acid - Lebedev, Vladimir; Lebedeva, Katerina; Cherkashina, Аnna; Petrushenko, Sergey; Bogatyrenko, Sergiy; Olkhovska, Аnzhela; Hrubnyk, Ihor; Maloshtan, Liudmyla; Kopach, Volodymyr; Klochko, Natalja (Journal of Research Updates in Polymer Science, 2024)
The work is devoted to the development of safe and biocompatible multicomponent gelatin-alginate hydrogels modified with humic acids (HA) and impregnated with the antifibrinolytic agent aminocaproic acid (АА).These hydrogels are designed to be effective hemostatic materials with anti-inflammatory properties and the ability to deliver in less than 30 seconds to deep and hidden areas of hemorrhages. Studies of the crystal structure by X-ray diffraction analysis and non-covalent interactions of molecules by Fourier transform infrared spectroscopy of the developed hemostatic gelatin-alginate hydrogels modified with bactericidal and anti-inflammatory humic acids made it possible to identify the optimal concentrations of HA from 2.5 wt.%. up to 5 wt.%. At such concentrations of HA, gelatin-alginate hydrogels have a semicrystalline structure. Due to non-covalent bonds between polymer chains, they are thermo-responsive with a gel-sol transition temperature of about 37 °C. Impregnation of these hydrogels with aminocaproic acid led to an almost threefold increase in their swelling, which facilitated the dissolution of AA in the hydrogels and its subsequent delivery to the wound. Experiments simulating the transmembrane transport of aminocaproic acid from the developed gelatin-alginate hydrogels confirmed their ability to rapidly deliver up to 494± 3 mg of AA from 5 ml of hydrogel to the wound.